Yield of colonoscopy with special reference to lower gastrointestinal bleeding in a tertiary referral center in Eastern India - Gautam Ray (Journal of Digestive Endoscopy, 2015)
Background: Little data exist on the yield of colonoscopy in its different indications, especially gastrointestinal (GI) bleeding. Furthermore, there are no formal guidelines regarding the timing of its performance in the work up for lower GI bleeding. Methods: In a retrospective study, spanning from January 2007 to December 2013, the clinical data of all the patients undergoing colonoscopy were retrieved from the hospital records including the predominant symptom which mandated colonoscopy and results of the other tests done before colonoscopy including upper GI endoscopy (esophagogastroduodenoscopy [EGD]). The type of GI bleed (overt or occult) along with the presence or absence of iron deficiency anemia (IDA) was noted. The yield of EGD in the corresponding years in those having a presentation with lower GI bleed and/or IDA was also noted for comparison. Results: Overall yield of colonoscopy was low (25.7%) like for all its indications except lower GI bleed where its yield was highest (45.2%). 81.2% of the cases with a diagnosis presented with lower GI bleed, highest for colon cancer (90%), and polyps (86.1%). Cases of occult bleed more often had a positive diagnosis than overt bleed (P = 0.02). EGD yielded positive findings in more cases (43.2%, P = 0.00) than colonoscopy (except piles). Colonic cancers and polyps were presented with hematochezia when compared to gastric cancer which presented more often with occult bleed and other clinical symptoms. Conclusion: EGD should be done first in lower GI bleeding to exclude upper GI source and select subsequent colonoscopy. For hematochezia and occult bleed, colonoscopy is important whether IDA is present or not.